2022
DOI: 10.3389/fendo.2022.861567
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering Obesity-Related Gene Clusters Unearths SOCS3 Immune Infiltrates and 5mC/m6A Modifiers in Ossification of Ligamentum Flavum Pathogenesis

Abstract: BackgroundOssification of ligamentum flavum (OLF) is an insidious and debilitating heterotopic ossifying disease with etiological heterogeneity and undefined pathogenesis. Obese individuals predispose to OLF, whereas the underlying connections between obesity phenotype and OLF pathomechanism are not fully understood. Therefore, this study aims to explore distinct obesity-related genes and their functional signatures in OLF.MethodsThe transcriptome sequencing data related to OLF were downloaded from the GSE1062… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…38,39 Some reports have indicated that a range of factors including genetics, metabolic abnormalities, inflammation, and mechanical stress contribute to TOLF incidence and progression. [40][41][42] Age, body mass index, and smoking have all been identified as independent risk factors associated with TOLF. [43][44][45][46] While overall disease incidence is low, TOLF patients frequently suffer from nerve damage 47,48 developing symptoms that progress with the increasing severity of spinal stenosis and spinal cord compression, culminating in complete paraplegia in some cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Some reports have indicated that a range of factors including genetics, metabolic abnormalities, inflammation, and mechanical stress contribute to TOLF incidence and progression. [40][41][42] Age, body mass index, and smoking have all been identified as independent risk factors associated with TOLF. [43][44][45][46] While overall disease incidence is low, TOLF patients frequently suffer from nerve damage 47,48 developing symptoms that progress with the increasing severity of spinal stenosis and spinal cord compression, culminating in complete paraplegia in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…Reports focused on OLF are increasing outside of East Asia as reported case numbers continue to climb 38,39 . Some reports have indicated that a range of factors including genetics, metabolic abnormalities, inflammation, and mechanical stress contribute to TOLF incidence and progression 40–42 . Age, body mass index, and smoking have all been identified as independent risk factors associated with TOLF 43–46 .…”
Section: Discussionmentioning
confidence: 99%
“…The pathological process of OLF was similar to that of endochondral ossification and was characterized by the formation of heterotopic mature bone, which involved several stages including chondrocyte proliferation, fibroblast hyperplasia, osteogenesis, and maturation [ 15 , 16 ]. Since there was a selectively high prevalence of the condition in certain geographic areas, the underlying mechanisms of OLF were initially considered to be primarily linked to congenital (genetic) factors; however, as research progressed, non-genetic (environmental) factors such as age, inflammation, biomechanics, and so on began to emerge, causing OLF to gradually be considered a multifactorial disease [ [3] , [4] , [5] ]. These risk factors largely overlapped with SOP, creating a complex relationship between OLF and SOP.…”
Section: Discussionmentioning
confidence: 99%
“…To forecast protein interactions and build a PPI network, SODEGs were uploaded to the STRING database ( http://string-db.org ). After taking into account the previous literature and our deliberations [ 3 , 12 , 13 ], an interaction score greater than 0.4 was finally chose to balance between including a sufficient number of potential interactions for downstream analysis and minimizing the inclusion of false positive interactions. The edge-betweenness and random walk methods were subsequently employed to emphasize sub-networks or neighborhoods of the gene connectivity data from the STRING database, and the divided clusters were then depicted by further function enrichment in R software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation